Differential diffusion effects during the ignition of a thermally stratified premixed hydrogen–air mixture subject to turbulence - Bisetti, Fabrizio; Chen, J.-Y.; Chen, Jacqueline H.; Hawkes, Evatt R. (Proceedings of the Combustion Institute, 2009)
Recent research efforts have focused on the usage of lean hydrogen–air mixtures in Homogeneous Charge Compression Ignition (HCCI) engines. In this work we investigate the effect of temperature stratification on the occurrence of differential diffusion during the autoignition of a lean premixed hydrogen–air mixture at high pressure, constant volume conditions. We employ a Direct Numerical Simulation methodology including hydrogen–air finite-rate chemistry and molecular transport based on a Lewis number formulation for individual species [E.R. Hawkes, R. Sankaran, P.P. Pébay, J.H. Chen, Combust. Flame 145 (1–2) (2006) 145–159]. At the highest level of temperature stratification tested, we find that differential diffusion has an impact on the heat release rate. Early in the ignition, regions with mixture fraction higher than the initial value are created by differential diffusion and they subsequently burn to achieve higher temperatures, which can be accounted for by simple equilibrium calculations. Later in the ignition process, differential diffusion enhances heat release rate along positively stretched fronts and reduces it for negatively stretched regions. Finally, it is found that mixture fraction is not a conserved scalar due to differential diffusion.